A new genus and six new species of endemic landhopper in the family Arcitalitridae (Amphipoda: Talitroidea) from New Zealand - Ball, Olivier J.-P.; Myers, Alan A.; Shepherd, Lara D. (Zootaxa, 2025)
Recently, the first representatives of endemic simplidactylate landhoppers in the ancient family Arcitalitridae were recognised from New Zealand. This study reveals the existence of a second endemic genus, Koekotroides gen. nov., from this family in New Zealand. Six new species of Koekotroides gen. nov. are described from native vegetation in the North Island of New Zealand and some of its offshore islands: K. moowhitihauuru sp. nov., K. taapinea sp. nov., K. tewhaarua sp. nov., K. maene sp. nov., K. pekehau sp. nov., and K. ngaokiroa sp. nov. Five of the six species were subjected to genetic investigation. There was generally good agreement between the taxon delineation determined from morphological analysis and that from sequence analysis of the mitochondrial 16S locus. The genus appears to have a centre of diversity in the northern North Island and the Three Kings and Poor Knights Islands each have their own species. Ancestors of Koekotroides presumably arrived in Zealandia before it rifted from Gondwana during the later Cretaceous. This brings the total number of described native landhopper species in New Zealand to 35 and increases the number of described arcitalitrids to nine.